Health Without Barrier: Improving Emotion Regulation through Psychoeducation in the Deaf Community - Muis, Ismarli; Agussalim, Amirah Aminanty (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Deaf individuals are a group with unique communication needs who often face challenges in understanding themselves and their psychological aspects. Access to knowledge about emotion regulation remains very limited for the Deaf community, primarily because mental health information is generally delivered verbally and rarely involves sign language interpreters. This community service program was designed to foster positive character and support the mental health of the Deaf community in Makassar City through a psychoeducational activity. The psychoeducational activity was delivered through a lecture, supported by PowerPoint visuals and Sign Language to ensure accessible communication for Deaf participants. The program was evaluated using digital pre-tests and post-tests administered via Google Forms. Analysis of data from 31 participants using a paired-samples t-test showed a significant difference (p = 0.000 < 0.05), indicating an increase in understanding of emotion regulation following the psychoeducation.